Language influences on numerical development—Inversion effects on multi-digit number processing - Klein, Elise; Bahnmuelller, Julia; Mann, Anne; Pixner, Silvia; Kaufmann, Liane; Nuerk, Hans-Christoph; Moeller, Korbinian (Frontiers in Psychology, 2013)
In early numerical development, children have to become familiar with the Arabic number system and its place-value structure. The present review summarizes and discusses evidence for language influences on the acquisition of the highly transparent structuring principles of digital-Arabic digits by means of its moderation through the transparency of the respective language’s number word system. In particular, the so-called inversion property (i.e., 24 named as ‘four and twenty’ instead of ‘twenty four’) was found to influence number processing in children not only in verbal but also in non-verbal numerical tasks. Additionally, there is first evidence suggesting that inversion-related difficulties may influence numerical processing longitudinally. Generally, language-specific influences in children’s numerical development are most pronounced for multi-digit numbers. Yet, there is currently only one study on three-digit number processing for German-speaking children. A direct comparison of additional new data from Italian-speaking children further corroborates the Whorfian claim that language impacts on all types of cognitive (number) processing as inversion-related interference was found most pronounced for German-speaking children. In sum, we conclude that numerical development may not be language-specific but seems to be moderated by language.